Combined Brain/Heart Magnetic Resonance Imaging in Systemic Lupus Erythematosus - Mavrogeni, Sophie (Curr Cardiol Rev, 2020)
Cardiovascular Disease (CVD) in Systemic Lupus Erythematosus (SLE) and Neuropsychiatric SLE (NPSLE) has an estimated prevalence of 50% and 40%, respectively and both constitute major causes of death among SLE patients. In this review, a combined brain/heart Magnetic Resonance Imaging (MRI) for SLE risk stratification has been proposed. The pathophysiologic background of NPSLE includes microangiopathy, macroscopic infarcts and accelerated atherosclerosis. Classic brain MRI findings demonstrate lesions suggestive of NPSLE in 50% of the NPSLE cases, while advanced MRI indices can detect pre-clinical lesions in the majority of them, but their clinical impact still remains unknown. Cardiac involvement in SLE includes myo-pericarditis, valvular disease/endocarditis, Heart Failure (HF), coronary macro-micro-vascular disease, vasculitis and pulmonary hypertension. Classic and advanced Cardiovascular Magnetic Resonance (CMR) indices allow function and tissue characterization for early diagnosis and treatment follow-up of CVD in SLE. Although currently, there are no clinical data supporting the combined use of brain/heart MRI in asymptomatic SLE, it may have a place in cases with clinical suspicion of brain/heart involvement, especially in patients at high risk for CVD/stroke such as SLE with antiphospholipid syndrome (SLE/APS), in whom concurrent cardiac and brain lesions have been identified. Furthermore, it may be of value in SLE with multi-organ involvement, NPSLE with concurrent cardiac involvement, and recent onset of arrhythmia and/or heart failure.